Morphological, Cytological and Molecular Studies and Feeding and Defecation Pattern of Hybrids from Experimental Crosses between Triatoma sordida and T. rosai (Hemiptera, Triatominae) - Vicente, Roberto Dezan [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Borsatto, Kelly Cristine [UNESP]; Garcia, Ariane Cristina Caris [UNESP]; Cristal, Daniel Cesaretto [UNESP]; Delgado, Luiza Maria Grzyb [UNESP]; Bittinelli, Isadora de Freitas [UNESP]; De Mello, Denis Vinicius [UNESP]; Dos Reis, Yago Visinho [UNESP]; Ravazi, Amanda [UNESP]; Galvão, Cleber; De Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; et al. (MDPI, 2022)
Under laboratory conditions, Triatoma rosai and T. sordida are able to cross and produce hybrids. In the face of climate and environmental changes, the study of hybrids of triatomines has evolutionary and epidemiological implications. Therefore, we performed morphological, cytological and molecular studies and characterized the feeding and defecation pattern of hybrids from crosses between T. sordida and T. rosai. The morphological characterization of the female genitalia of the hybrids showed that characteristics of both parental species segregated in the hybrids. Cytogenetic analyzes of hybrids showed regular metaphases. According to molecular studies, the mitochondrial marker Cytochrome B (CytB) related the hybrids with T. sordida and the nuclear marker Internal Transcribed Spacer 1 (ITS-1) related the hybrids with T. rosai. Both parents and hybrids defecated during the blood meal. Thus, the hybrids resulting from the cross between T. sordida and T. rosai presented segregation of phenotypic characters of both parental species, 100% homeology between homeologous chromosomes, phylogenetic relationship with T sordida and with T. rosai (with CytB and ITS-1, respectively), and, finally, feeding and defecation patterns similar to the parents.
Keywords: Chagas disease vectors; cytogenetics; hybridization; molecular biology; morphology